Co‐evolution of MHC class I and variable NK cell receptors in placental mammals. Issue 1 (September 2015) - Guethlein, Lisbeth A.; Norman, Paul J.; Hilton, Hugo H. G.; Parham, Peter
Summary: Shaping natural killer (NK) cell functions in human immunity and reproduction are diverse killer cell immunoglobulin‐like receptors (KIRs) that recognize polymorphic MHC class I determinants. A survey of placental mammals suggests that KIRs serve as variable NK cell receptors only in certain primates and artiodactyls. Divergence of the functional and variable KIRs in primates and artiodactyls predates placental reproduction. Among artiodactyls, cattle but not pigs have diverse KIRs. Catarrhine (humans, apes, and Old World monkeys) and platyrrhine (New World monkeys) primates, but not prosimians, have diverse KIRs. Platyrrhine and catarrhine systems of KIR and MHC class I are highly diverged, but within the catarrhines, a stepwise co‐evolution of MHC class I and KIR is discerned. In Old World monkeys, diversification focuses on MHC‐A and MHC‐B and their cognate lineage II KIR. With evolution of C1‐bearing MHC‐C from MHC‐B, as informed by orangutan, the focus changes to MHC‐C and its cognate lineage III KIR. Evolution of C2 from C1 and fixation of MHC‐C drove further elaboration of MHC‐C‐specific KIR, as exemplified by chimpanzee. In humans, the evolutionary trajectory changes again. Emerging from reorganization of the KIR locus and selective attenuation of KIR avidity for MHC class I are the functionally distinctive KIR A and KIR B haplotypes.